2012
DOI: 10.3168/jds.2011-4582
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic yogurts manufactured with increased glucose oxidase levels: Postacidification, proteolytic patterns, survival of probiotic microorganisms, production of organic acid and aroma compounds

Abstract: We investigated the effect of increased glucose oxidase concentration as a technological option to decrease oxidative stress during the processing of probiotic yogurts. Probiotic yogurts were produced with increased concentrations of glucose oxidase (0, 250, 500, 750, or 1,000 mg/kg) and submitted to physicochemical and microbiological analysis at 1, 15, and 30 d of refrigerated storage. Higher concentrations of glucose oxidase (750 and 1,000 mg/kg) and a longer storage time were found to have an influence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 70 publications
8
55
0
1
Order By: Relevance
“…Proteinase and peptidases constitute the primary enzymes in LAB responsible for proteolysis of caseins as a source of amino acids and nitrogen for LAB (Shihata and Shah 2000). Cruz and others (2012) reported that higher concentrations of glucose oxidase (750 to 1,000 mg/kg) and storage period had an influence on characteristics of probiotic yogurt and resulted in more postacidification and higher proteolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Proteinase and peptidases constitute the primary enzymes in LAB responsible for proteolysis of caseins as a source of amino acids and nitrogen for LAB (Shihata and Shah 2000). Cruz and others (2012) reported that higher concentrations of glucose oxidase (750 to 1,000 mg/kg) and storage period had an influence on characteristics of probiotic yogurt and resulted in more postacidification and higher proteolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Applications of GO include use in biosensors, biofuel cells, as well as in food products45. Considering applications in food, GO has been used to reduce browning caused by the Maillard reaction6; the oxygen scavenging activity of GO and simultaneous production of H 2 O 2 can also reduce food spoilage78. Moreover, the production of H 2 O 2 can improve dough stability by forming cross linkages within gluten9; production of H 2 O 2 can also oxidize water-soluble pentosans10, which then gelate and increase water uptake and softness of baked products11.…”
mentioning
confidence: 99%
“…A ocorrência de acetaldeído, acetona e diacetil em iogurtes é descrita na literatura (CRUZ et al, 2012) (GEORGALA et al, 1995).…”
unclassified